Local c-di-GMP signaling, triggered by cross-regulation of cAMP-CRP and c-di-GMP, controls biofilm formation under nutrient limitation - Di Sun; Xiaobo Liu; Ying Zhang; Rui Shi; Yunrui Ru; Xuge Zhou; Ying Chen; Jing Yang; Jiawen Liu; Jingrong Zhu; Cong Liu; Weijie Liu (Proceedings of the National Academy of Sciences, 2025)
Bacteria have several nucleotide second messengers, most of which act as global regulators to control a wide range of bacterial physiological processes. Studies usually focus on a single second messenger, and the mechanisms and physiological significance of the cross-regulation between different nucleotide second messengers are often unclear. Here, we show that Shewanella putrefaciens can form biofilms in both nutrient-rich and nutrient-poor media. While both are controlled by c-di-GMP, the regulatory models differ. Under low nutrient conditions, cross-regulation of cAMP-CRP and c-di-GMP occurs at the transcriptional and posttranslational levels, thereby controlling biofilm development. During the early stages of biofilm development, cAMP-CRP directly promotes the transcription of a PDE gene, lrbR , by LrbA. Additionally, cAMP-CRP recruits LrbR to BpfD to suppress early biofilm formation via LrbR-dependent local degradation of c-di-GMP. Finally, as intracellular LrbR levels decrease, cAMP-CRP-BpfD enables a rapid shift to biofilm development and supports biofilm maintenance. Under high nutrient conditions, this cross-regulation does not occur, resulting in a positive correlation between global c-di-GMP levels and biofilm biomass. The identification of distinct modes of biofilm regulation in different nutrients will provide a theoretical basis for future targeted control of biofilm formation in different nutrient environments.